Chronic erosive seropositive arthritis in a patient with chronic hepatitis C - L P Ananjeva; N V Ignatova; A V Smirnov (Научно-практическая ревматология, 2008)
Joint syndrome evolution was prospectively followed up in a 49-year-old woman who had serum hepatitis in 1990. When she came to a rheumatologist for the first time in 1999 she complained of occasional joint pain. She did not have joint inflammatory changes at that time but chronic hepatitis С was revealed at the examination. Hepatitis С diagnosis was confirmed by morphological and repeated virological evaluations. During antiviral treatment the pt developed symmetrical polyarthritis involving hand joints. Elevation of cryoglobuline, rheumatoid factor and antinuclear antibodies level was revealed. During the next year polyarthritis recurred and later acquired undulatory course with periods of exacerbation and stabilization. Attempts of treatment with sulfasalazine failed due to transaminase elevation. In 2006 ulnar deviation appeared and rheumatoid factor level remained elevated. MRI showed multiple erosions of carpal bones. Considering features of joint syndrome development joint damage in this pt was regarded as arthritis associated with chronic hepatitis C.